A Nanopore‐Based Saccharide Sensor. Issue 33 (11th July 2022) - Zhang, Shanyu; Cao, Zhenyuan; Fan, Pingping; Wang, Yuqin; Jia, Wendong; Wang, Liying; Wang, Kefan; Liu, Yao; Du, Xiaoyu; Hu, Chengzhen; Zhang, Panke; Chen, Hong‐Yuan; et al.
Abstract: Saccharides play critical roles in many forms of cellular activities. Saccharide structures are however complicated and similar, setting a technical hurdle for direct identification. Nanopores, which are emerging single molecule tools sensitive to minor structural differences between analytes, can be engineered to identity saccharides. A hetero‐octameric Mycobacterium smegmatis porin A nanopore containing a phenylboronic acid was prepared, and was able to clearly identify nine monosaccharide types, including D‐fructose, D‐galactose, D‐mannose, D‐glucose, L‐sorbose, D‐ribose, D‐xylose, L‐rhamnose and N‐acetyl‐D‐galactosamine. Minor structural differences between saccharide epimers can also be distinguished. To assist automatic event classification, a machine learning algorithm was developed, with which a general accuracy score of 0.96 was achieved. This sensing strategy is generally suitable for other saccharide types and may bring new insights to nanopore saccharide sequencing. Abstract : A heterogeneously assembled MspA nanopore is reported. When modified with a single phenylboronic acid adapter, it can be applied in the identification of monosaccharides at the single‐molecule level.